2020
DOI: 10.1038/s41598-020-68594-y
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor alpha is involved in the temperature-induced sex differentiation of a vertebrate

Abstract: Medaka (Oryzias latipes) is a teleost fish with an XX/XY sex determination system, similar to that of mammals. However, under high temperature conditions, XX medaka is masculinised by elevation of cortisol, the major teleost glucocorticoid. in this study, to identify novel factors in the gonads acting downstream from cortisol during sexual differentiation, we performed RNA sequencing (RNA-seq) analysis using the gonadal regions of larvae reared at normal temperature with and without cortisol, and at high tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…In addition, the prevalence of some diseases is different by gender [73], and many experiments also show that PPARs are different in function by gender. PPARα expression is more abundant in native and activated male T cells than in female cells [74,75], suggesting that PPARα has a more substantial role in male T cells than in female T cells. Likewise, multiple studies have shown that the male hormone androgen has been suggested to influence the expression of PPARα in male T cells [76][77][78].…”
Section: Pparβ/δmentioning
confidence: 99%
“…In addition, the prevalence of some diseases is different by gender [73], and many experiments also show that PPARs are different in function by gender. PPARα expression is more abundant in native and activated male T cells than in female cells [74,75], suggesting that PPARα has a more substantial role in male T cells than in female T cells. Likewise, multiple studies have shown that the male hormone androgen has been suggested to influence the expression of PPARα in male T cells [76][77][78].…”
Section: Pparβ/δmentioning
confidence: 99%
“…Wild-type, pparaa KO ( 20 ), and gsdf KO lines ( 32 ) originating from an FLFII medaka line ( 33 ) were used in this study. pparaa KO and gsdf KO lines were generated using the CRISPR/Cas9 system and maintained by brother-sister mating of the genetically homogenous medaka ( 20 , 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type, pparaa KO ( 20 ), and gsdf KO lines ( 32 ) originating from an FLFII medaka line ( 33 ) were used in this study. pparaa KO and gsdf KO lines were generated using the CRISPR/Cas9 system and maintained by brother-sister mating of the genetically homogenous medaka ( 20 , 32 ). pparaa KO and gsdf KO XX medaka do not masculinize with cortisol treatment ( 20 , 32 ), while some gsdf KO but not pparaa KO XY fish become females having ovaries under normal conditions, while others become normal males having testes ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differentiation is the product of a combative relationship between genes involved in the development and maturation of testis and ovary [23,24]. The environmental factors here are temperature [25], pH [26], population density [27], oxygen concentration [28], and social status [29]. However, at this stage, the involvement of environmental factors is more on maintaining the activation and suppression of various male and female pathways depending on the sexual fate.…”
Section: Introductionmentioning
confidence: 99%